Motivasi Siswa dalam Mengikuti Pembelajaran Pendidikan Jasmani pada Masa Pandemi di SMA Negeri Kota Samarinda - didik cahyono (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the results of the motivation survey of class X students in participating in physical education learning at SMA Negeri 17 Samarinda in the academic year 2020/2021 during the Covud - 19 pandemic. This research is a descriptive study. The method used is a survey with data collection techniques using a questionnaire. The subjects in this study were students at state high school 17 Samarinda. The trial was carried out with a validity coefficient of 0.312 and a reliability of 0.900. The data analysis technique used quantitative descriptive analysis which was stated in the form of a percentage. After conducting the research, the following results were obtained, the average descriptive statistical score of 108.88 was in the medium category and based on the motivation frequency distribution in the very low category of 7.77% (15 students / i), low 18.14% (35 students / i), moderate 46.63% (90 students / i), high 21.24% (41 students / i), and very high category 6.22% (12 students / i). From the results that have been obtained, the highest percentage is the medium category based on indicators in intrinsic factors and indicators in extrinsic factors.